Effect of Paxlovid in COVID-19 treatment during the periods of SARS-CoV-2 Omicron BA.5 and BN.1 subvariant dominance in the Republic of Korea: a retrospective cohort study - Dong-Hwi Kim; Min-Gyu Yoo; Na-Young Kim; So Young Choi; Minjeong Jang; Misuk An; Se-Jin Jeong; Jungyeon Kim (Osong Public Health and Research Perspectives, 2024)
Objectives This study was conducted to assess the efficacy of nirmatrelvir/ritonavir treatment in patients with coronavirus disease 2019 (COVID-19), particularly those aged 60 years and older. Using real-world data, the period during which the BN.1 Omicron variant was dominant was compared to the period dominated by the BA.5 variant. Methods In this retrospective cohort study, data were collected regarding 2,665,281 patients infected with severe acute respiratory syndrome coronavirus 2 between July 24, 2022, and March 31, 2023. Propensity score matching was utilized to match patients who received nirmatrelvir/ritonavir in a 1:4 ratio between BN.1 and BA.5 variant groups. Multivariable logistic regression analysis was employed to assess the effects of nirmatrelvir/ritonavir within these groups. Results Compared to the prior period, the efficacy of nirmatrelvir/ritonavir did not significantly differ during the interval of Omicron BN.1 variant dominance in the Republic of Korea. Among patients treated with nirmatrelvir/ritonavir, a significantly lower risk of mortality was observed in the BN.1 group (odds ratio [OR], 0.698; 95% confidence interval [CI], 0.557–0.875) compared to the BA.5 group. However, this treatment did not significantly reduce the risk of severe or critical illness, including death, for those in the BN.1 group (OR, 0.856; 95% CI, 0.728–1.007). Conclusion Nirmatrelvir/ritonavir has maintained its effectiveness against COVID-19, even with the emergence of the BN.1 Omicron subvariant. Consequently, we strongly recommend the administration of nirmatrelvir/ritonavir to patients exhibiting COVID-19-related symptoms, irrespective of the dominant Omicron variant or their vaccination status, to mitigate disease severity and decrease the risk of mortality.